Stability and Change in Adjustment Profiles Among Chinese American Adolescents: The Role of Parenting. - Kim, Su; Wang, Yijie; Shen, Yishan; Hou, Yang (Journal of Youth & Adolescence, 2015)
Asian American adolescents are often depicted as academically successful but psychologically distressed, a pattern known as the achievement/adjustment paradox. In a sample of 444 Chinese American adolescents (54 % females), we identified three distinct patterns of adjustment in early adolescence, middle adolescence, and emerging adulthood: the well- adjusted group, which was the largest, exhibited high achievement and low psychological distress; the poorly- adjusted group exhibited poor achievement and moderate distress; and the paradox group exhibited relatively high achievement and high distress. More than half of the adolescents remained in the same profile over time. Adolescents with supportive parents were more likely to stay well-adjusted, and those with 'tiger' parents were more likely to stay in the paradox group over time. The present study focused on the critical role of parenting in early adolescence, highlighting variations in Chinese American adolescents' adjustment in multiple domains over time.